Lymphocytic Hypophysitis Presenting as Acute-onset Arginine Vasopressin Deficiency and Pituitary Stalk Thickening: A Case Report - Yang, Lian Zi; Velaiutham, Shanty (Journal of the ASEAN Federation of Endocrine Societies, 2025)
Lymphocytic hypophysitis (LHy) is a rare autoimmune inflammatory process that selectively affects the neurohypophysis and infundibulum, typically presenting with arginine vasopressin deficiency (AVP-D). On magnetic resonance imaging (MRI) with contrast, there is a thickening of the pituitary stalk, enlargement of the neurohypophysis or both with homogeneous enhancement. LHy can be self-limiting and regression can be seen radiologically during follow-up. A 22-year-old male presented with clinical findings consistent with AVP-D in 2016. MRI brain demonstrated enlargement of the pituitary stalk and absence of a posterior pituitary bright spot. He was given a trial of glucocorticoid treatment. His serial MRI brain showed a reduction of the pituitary stalk, but the AVP-D persisted. He was diagnosed with LHy. LHy is characterized by lymphocytic infiltration, leading to eventual destruction of the pituitary tissue accompanied by varying degrees of pituitary dysfunction. Definite diagnosis can only be established via pituitary stalk biopsy. Due to the wide range of possible aetiologies, close monitoring is strongly recommended for the treatment of presumed cases lacking histopathologic confirmation. The response rate to glucocorticoids has been variable. Periodic monitoring of anterior pituitary function and pituitary MRI are essential in the management of this condition.